A randomized, multinational, noninferiority, phase III trial to evaluate the safety and efficacy of BF‐200 aminolaevulinic acid gel vs. methyl aminolaevulinate cream in the treatment of nonaggressive basal cell carcinoma with photodynamic therapy3. (16th May 2018) - Morton, C.A.; Dominicus, R.; Radny, P.; Dirschka, T.; Hauschild, A.; Reinhold, U.; Aschoff, R.; Ulrich, M.; Keohane, S.; Ekanayake‐Bohlig, S.; Ibbotson, S.; Ostendorf, R.; et al.
Summary: Background: Basal cell carcinoma (BCC) represents the most common nonmelanoma skin cancer worldwide, affecting mainly adult, fair‐skinned individuals. The World Health Organization distinguishes aggressive and nonaggressive forms, of which prototypical variants of the latter are primary nodular and superficial BCC. Objectives: To demonstrate noninferiority of BF‐200 ALA (a nanoemulsion gel containing 5‐aminolaevulinic acid) compared with MAL (a cream containing methyl aminolaevulinate) in the treatment of nonaggressive BCC with photodynamic therapy (PDT). Noninferiority of the primary efficacy variable (overall patient complete response 12 weeks after last PDT) would be declared if the mean response for BF‐200 ALA was no worse than that for MAL, within a statistical margin of Δ = −15%. Methods: The study was a randomized, phase III trial performed in Germany and the U.K. with ongoing 5‐year follow‐up. Of 281 randomized patients, 138 were treated with BF‐200 ALA and 143 with MAL. Patients received two PDT sessions 1 week apart. Remaining lesions 12 weeks after the second PDT were retreated. Illumination was performed with a red light source (635 nm, 37 J cm −2 ). The results shown include clinical end points and patients' reassessment 12 months after the last PDT. The study was registered with EudraCT (number 2013‐003241‐42). Results: Of the BF‐200 ALA‐treated patients, 93·4% were complete responders compared with 91·8% in the MAL group. The difference of means was 1·6, with a one‐sided 97·5% confidence interval of −6·5, establishing noninferiority ( P < 0·0001). The results for secondary efficacy parameters were in line with the primary outcome. Recurrence rates 12 months after the last treatment were ≤ 10%. Conclusions: Treatment of nonaggressive BCC with BF‐200 ALA‐PDT is highly effective and well tolerated with proven noninferiority to MAL‐PDT. It demonstrates low recurrence rates after 1 year of follow‐up. Abstract : What's already known about this topic? Photodynamic therapy (PDT) using BF‐200 aminolaevulinic acid (ALA) gel is registered and highly effective in the treatment of mild‐to‐moderate actinic keratosis and field cancerization. BF‐200 ALA gel was recently approved for the treatment of superficial and/or nodular basal cell carcinoma (BCC) unsuitable for surgical treatment. PDT using methyl aminolaevulinate (MAL) cream is approved for the treatment of thin or nonhyperkeratotic and nonpigmented actinic keratoses, Bowen disease, and superficial and nodular BCCs when other therapies are considered less appropriate. What does this study add? BF‐200 ALA‐PDT is confirmed to be significantly noninferior to MAL‐PDT for the treatment of nonaggressive BCC. Treatment‐emergent adverse events were comparable between the two patient groups, with similar or slightly lower recurrence rates for BF‐200 ALA gel compared with MAL cream after 12 months. Plain language summary available online Respond to this article